Association of periodontal therapy, with inflammatory biomarkers and complications in COVID-19 patients: a case control study - Khalid N. Said (14150715) (2022)
Background In previous studies, COVID-19 complications were reported to be associated with periodontitis. Accordingly, this study was designed to test the hypothesis that a history of periodontal therapy could be associated with lower risk of COVID-19 complications. Methods A case–control study was performed using the medical health records of COVID-19 patients in the State of Qatar between March 2020 and February 2021 and dental records between January 2017 and December 2021. Cases were defined as COVID-19 patients who suffered complications (death, ICU admissions and/or mechanical ventilation); controls were COVID-19 patients who recovered without major complications. Associations between a history of periodontal therapy and COVID-19 complications were analysed using logistic regression models adjusted for demographic and medical factors. Blood parameters were compared using Kruskal–Wallis test. Results In total, 1,325 patients were included. Adjusted odds ratio (AOR) analysis revealed that non-treated periodontitis was associated with significant risk of need for mechanical ventilation (AOR = 3.91, 95% CI 1.21–12.57, p = 0.022) compared to periodontally healthy patients, while treated periodontitis was not (AOR = 1.28, 95% CI 0.25–6.58, p = 0.768). Blood analyses revealed that periodontitis patients with a history of periodontal therapy had significantly lower levels of D-dimer and Ferritin than non-treated periodontitis patients. Conclusion Among COVID-19 patients with periodontal bone loss, only those that have not received periodontal therapy had higher risk of need for assisted ventilation. COVID-19 patients with a history of periodontal therapy were associated with significantly lower D-dimer levels than those without recent records of periodontal therapy. Clinical relevance The fact that patients with treated periodontitis were less likely to suffer COVID-19 complications than non-treated ones further strengthen the hypothesis linking periodontitis to COVID-19 complications and suggests that managing periodontitis could help reduce the risk for COVID-19 complications, although future research is needed to verify this. Other Information Published in: Clinical Oral Investigations License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s00784-022-04631-6